Střednědobé výsledky rekonstrukce Charcotovy neuropatické artropatie nohy u diabetiků - Kučera, Tomáš; Grinac, Michal; Valtr, Ondřej; Šponer, Pavel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2019)
PURPOSE OF THE STUDY The aim of this study was to evaluate the mid-term outcomes of the surgical reconstruction of Charcot Foot Neuroarthropathy in diabetic patients with failed conservative treatment and indicated for a below-knee amputation. MATERIAL AND METHODS In the period from 2010 to 2015 the surgical reconstruction of inactive, chronic Charcot Foot Neuroarthropathy classified as type II and III by Sanders and Frykbeg was performed in 16 patients with failed conservative treatment. All these patients were by the diabetes centres initially indicated for a below-knee amputation. The performed evaluation focused on the clinical outcome (limb preservation, walking in footwear, full weight-bearing capability, the radiographic result (talar-first metatarsal angle, calcaneal inclination - negative, neutral, positive), complications (associated and not associated with the surgery). RESULTS The mean follow-up period was 4.7 years (2.5-7.5 years). From the original group of 16 patients indicated for a below-knee amputation following the failure of conservative treatment, the amputation was performed in one patient only. After the surgical reconstruction 15 patients were able to fully weight-bear when achieving plantigrade foot position, of whom 9 wore regular footwear and 6 customised diabetic footwear. The talar-first metatarsal angle was corrected from the mean 30 degrees (20-45) to the mean 5 degrees (0-10). The calcaneal inclination was corrected from the negative preoperative value in all the cases to neutral in 5 patients and positive in 10 patients. The surgery-associated complications were the following: infectious complications - positive preoperative cultivation in 10 out of 16 patients, secondary healing of the surgical wound in 7 patients, the need of additional ablation of plantar prominence of tarsal skeleton in 2 patients, screw prominence in 2 patients with the need of extraction - all healed without complications. In one case a lower limb amputation was performed due to secondary limb ischemia. The complications not associated with the surgery consisted of a soft tissue injury due to neuropathy. DISCUSSION Conservative treatment remains the basic approach to Charcot foot neuroarthropathy which is often associated with a long-term off-loading of the affected limb on a wheelchair, repeated hospital stays, changes of wound dressing of plantar ulcers. These are stated as the most frequent indications for a major amputation. Nonetheless, even the major amputation is accompanied by complications. The candidate for a reconstruction surgery should be a cooperating, compensated, informed diabetic patient with Charcot foot neuroarthropathy, either instable or stable, but non-plantigrade. It is necessary to diagnose and treat the impairment of leg blood supply and osteomyelitis, and to provide an appropriate rehabilitation. CONCLUSIONS Of the original 16 indications for a lower limb amputation in diabetic patients with Charcot foot neuroarthropathy, only one amputation was performed. Positive mid-term outcomes of surgical reconstruction justify further development of this method, bearing in mind the necessity of careful indication and preoperative preparation of the patient in cooperation with diabetologists. Precise and accurate surgical technique and relevant postoperative care are essential to minimise the potential complications. Key words:Charcot arthropathy, diabetic neuropathy, rocker - bottom foot deformity, foot reconstruction.
Keywords: Foot; Amputation, Surgical; neuropatická artropatie; Plastic Surgery Procedures; lidé; Arthropathy, Neurogenic; Diabetic Foot; zákroky plastické chirurgie; Humans; noha (od hlezna dolů); amputace; diabetická noha